The Psychological Impact of Information and Communication Technology on Human Behavior and Mental Health: A Case Study of Kabul University, Afghanistan - Munir Ahmad Haqhparast; Abdul Wali Sirat; Bilal Himmat (Gameology and Multimedia Expert, 2026)
The rapid proliferation of Information and Communication Technology (ICT) has fundamentally transformed human interaction, cognition, and psychological well-being globally. In developing nations like Afghanistan, this transformation carries unique socio-cultural complexities that remain largely understudied. This study investigates the psychological impact of ICT usage on human behavior and mental health among students at Kabul University, Afghanistan. A mixed-methods approach was adopted, combining a structured questionnaire survey (n = 320) administered to undergraduate and postgraduate students with semi-structured interviews (n = 30). Validated instruments including the Internet Addiction Test (IAT), the Generalized Anxiety Disorder scale (GAD-7), and the Patient Health Questionnaire (PHQ-9) were employed. Quantitative data were analyzed using SPSS v.26, applying descriptive statistics, Pearson correlation, and multiple regression. Thematic analysis was conducted for qualitative data. Findings revealed that 38.4% of respondents exhibited moderate to severe internet addiction symptoms. Significant positive correlations were found between excessive ICT use and levels of anxiety (r = 0.61, p < 0.01) and depression (r = 0.54, p < 0.01). Qualitative themes indicated that ICT facilitated academic learning and social connectivity, while simultaneously contributing to sleep disturbance, social isolation, and reduced attention span. ICT exerts a dual influence on mental health at Kabul University   offering educational and communicative benefits while posing significant psychological risks, particularly for heavy users. Institutional interventions, digital literacy programs, and mental health support services are urgently recommended.